Fluorescence Diagnostics of Colon Malignant and Premalignant Lesions Using 5-Aminolevulinic Acid - Elena V. Filonenko; Andrey D. Kaprin; Antonina A. Raszhivina; Antonina N. Urlova; Andrey M. Nechipai (International Journal of Photoenergy)
Improvement of colon cancer diagnosis is a very important medical problem. Methods of fluorescence diagnosis (FD) with 5-aminolevulinic acid (5-ALA) have been used in detection of early cancer on the surface of mucosa. The objective of the study was to estimate the effectiveness of FD with 5-ALA in the detection of malignant lesions in the colon. From 2008 to 2010 full examinations have been performed in 78 patients suffering from colon polyps. For the study we used drug Alasens based on 5-ALA. Fluorescence colonoscopy with Alasens was made using the visual assessment of fluorescence images in combination with local fluorescence spectroscopy. The results of FD were compared with those of final histopathological study. The application of the method during colonoscopy allows specifying diagnosis, identifying areas of colon tumors transformation, and also showing a place for targeted biopsy. Sensitivity and specificity of FD with Alasens were 94.9% and 62.5%, respectively. The application of local fluorescence spectroscopy as a step of the combined approach allows increasing the specificity of fluorescence colonoscopy from 62.5% up to 93.7%.